Anti-inflammatory properties of menthol and menthone in Schistosoma mansoni infection - Zaia, Mauricio G. (2018)
Schistosomiasis is a parasitic disease caused by several species of trematode worms and it is believed that more than 261 million people are affected worldwide. New drug development has become essential because there is a risk of the parasite becoming resistant to Praziquantel, the only drug available for this infection. This study evaluated parasitological, immunological and histological parameters in mice infected with Schistosoma mansoni and treated with an herbal commercial medicine. This drug consists of menthol (30-55%) and menthone (14-32%). A 60 day treatment regimen with the herbal medicine decreased the number of S. mansoni eggs in the feces, liver, and intestine and reduced the number of hepatic granulomas. We observed a reduction of 84% in blood eosinophilia and a decrease in the IL-4 and IL-10 blood levels after treatment. Therefore, we propose that schistosomiasis treatment with this herbal medicine for 60 days has an immunomodulatory and anti-inflammatory action in this animal model for schistosomiasis thus contributing to the decrease in physio pathological effects caused by S. mansoni infection.